Accelerated landings in stingless bees are triggered by visual threshold cues. (26th August 2020) - Tichit, Pierre; Alves-dos-Santos, Isabel; Dacke, Marie; Baird, Emily
Abstract : Most flying animals rely primarily on visual cues to coordinate and control their trajectory when landing. Studies of visually guided landing typically involve animals that decrease their speed before touchdown. Here, we investigate the control strategy of the stingless bee Scaptotrigona depilis, which instead accelerates when landing on its narrow hive entrance. By presenting artificial targets that resemble the entrance at different locations on the hive, we show that these accelerated landings are triggered by visual cues. We also found that S. depilis initiated landing and extended their legs when the angular size of the target reached a given threshold. Regardless of target size, the magnitude of acceleration was the same and the bees aimed for the same relative position on the target suggesting that S. depilis use a computationally simple but elegant 'stereotyped' landing strategy that requires few visual cues.